(untitled) (Advancements in Homeopathic Research, 2022)
Chalazion is a painless, round swelling in the eyelid unless gets infected with pyogenic organisms. It mainly causes a cosmetic disturbance to patient. It is treated usually with intralesional corticosteroid injection or with incision and curetting. However this conventional treatment is associated with chances of recurrence or steroid induced complications. Homoeopathy has mentioned treatment for Chalazion and has been used in clinical practice. A retrospective study from OPD cases of institute was carried out with an aim to know the effectiveness of homoeopathy and biochemic medicines in Chalazion. Total 21 patients registered during the year 2003 to 2006 were studied irrespective of their age, gender and socioeconomic status. 5 cases presented with acute inflamed stage were resolved with homoeopathic Hepar sulphuris 200C. During non inflamed stage homoeopathic Con., Nat. mur., Silicea and biochemic Calc. flur., Natrum sulph. medicines were used. Out of 21 subjects, in15 (71%) Chalazion has resolved completely without any recurrence. Whereas in 4 subjects (19%) it was reduced but they were lost to follow-up. In 2 subjects (9.5%) there was no change. Thus medicines were found effective in in treating Chalazion in majority of subjects without any recurrence and untoward effects.